Konsep Memanusiakan Manusia Lewat Budaya Pada Pengembangan Panti Asuhan Di Kabupaten Tabanan - I Putu Angga Setiawan; I Nyoman Nuri Arthana; Agus Kurniawan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
An orphanage is a place to care for and care for orphans or orphans, less fortunate children. According to data from the social Ministry, currently. orphans in Indonesia is 4,023,622, consisting of 20,000 children who have been abandoned by their parents due to Covid-19; 45,000 children cared for by LKSA, and 3,978,622 children are cared for by poor families. planning and design of this orphanage, 2 main design problems were faced including (1) atmosphere (2) facilities, as a place for shelter and a place to educate children, to accommodate abandoned children, by providing care for the role of substitute parents through the care of Foster Mothers and Foster Fathers, and with the Development carried out to Increase the Capacity of Actors and Facilities and Add to the fulfillment of the Educational Function at the Orphanage, which is realized by Informal Schools to develop children's education, then this orphanage accommodates 2 main functions (1) Residential Functions realized by Orphanages and (2) Educational Functions realized by Informal Schools. Tabanan Regency was choosing because the object Development of the Orphanage was in that location, correctly in Tabanan Regency, Selemadeg Timur District, Bantas Village name Sos Children's Bali Orphanage.